INFORMATION AND COMMUNICATION TECHNOLOGIES IN DIGITAL ADVERTISING - MOROZ, Olena; KUSHCH, Anastasiia; BUNAK, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article explores the growing role of information and communication technologies in the digital advertising landscape, focusing on how these tools enhance the effectiveness, interactivity, and personalization of modern advertising campaigns. The rapid development of technologies such as artificial intelligence, cloud computing, Big Data analytics, and automated targeting systems has reshaped the advertising strategies of global brands and SMEs alike. Special attention is given to the implementation of ICT tools in leading digital platforms, which leverage user data and behavior prediction algorithms to deliver highly targeted, data-driven advertising experiences. The paper examines the key benefits of ICT in digital advertising, including increased efficiency, automation, real-time analytics, and adaptive content delivery. It also provides a comparative analysis of different types of ICT used in advertising, structured in a detailed classification table. Furthermore, the study identifies the main challenges associated with the use of ICT, such as cybersecurity threats, ethical concerns, and the need to comply with personal data protection regulations. By examining the advantages and challenges associated with ICT integration, such as improved targeting capabilities and concerns over data privacy, the research provides a comprehensive analysis of how these technologies reshape the advertising landscape.The article concludes that the integration of ICT in digital advertising is not only a competitive advantage but a necessity in the era of digital transformation. It also emphasizes the importance of strategic management in selecting and implementing these technologies in a way that aligns with organizational goals and audience expectations. The article concludes with practical recommendations for enterprises aiming to leverage ICT effectively in their advertising endeavors, thereby enhancing customer engagement and achieving strategic marketing objectives.
Keywords: information and communication technologies; digital advertising; personalization; artificial intelligence; marketing